Implementation of Worksheet Based Inquiry Lesson to Improve Student Numeracy Ability in Human Digestive System Material - Oktaviana, Rina; Nuraeni*, Eni; Amprasto, Amprasto; Qurota Aini, Rahmi (Jurnal Pendidikan Sains Indonesia, 2024)
The lack of students numeracy skills is caused by low inquiry abilities in the learning process. This problem is one of the factors that affect students' learning independence. To improves students thinking or numeracy skills, this study aims to investigate students preliminary science and numerical literacy in one of public school located in Bandung Regency. Students literacy skills were assessed prior to the implementation of learning strategies or media aimed to promote their literacy ability. This research aims to analyze the improvement in numeracy literacy skills through the implementation of Inquiry Lesson-based worksheets focused on the topic of human digestive system. The research employed a quasi-experimental method with a pre-test and post-test non-randomized control group design. Participants were selected from two science classes in 11th grade (XI MIPA) using cluster random sampling technique. The results showed that there was a significant difference with the experiment group demonstrating a higher increase in numeracy ability compared to control group, indicated by the N-gain value. Therefore, the implementation of Inquiry Lesson-based worksheets able to improve students numeracy skills